The effect of different seating conditions, in aircrafts, on passenger comfort and the use of cabin space - Olley, Emma-Jane (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2017)
Although aircraft cabin design has improved over the years, passengers continue to complain about sitting discomfort whilst flying. These complaints are often centred on the cramped and restricted seating conditions. Whilst passenger comfort is important, in order for airline companies to attract and retain customers, it is also important to design for cabin space needs. Denel Aviation intends to build a South African Regional Aircraft (SARA) that will fly point-to-point, linking regional centres and intends to design aircraft seats that not only optimise passenger comfort, but which also save cabin space. The aim of this investigation was two-fold. The first aim was to determine how aircraft backrest angle affected passenger comfort, ease of seat access, perceived restriction and legroom, with different seat pan angles and seat heights. The second aim was to determine whether passenger comfort was affected with the most preferred backrest angle for each seat pan angle and seat height. Determining how seat pan angle and seat height affect the preferred angle of the backrest was considered important as Denel intend to use aircraft seats with a non-adjustable backrest angle. For this study, 80 participants were recruited from Rhodes University and the general Grahamstown population. The participants consisted of 40 males and 40 females and were not limited by race, ethnicity or culture. The participants were classified into two age groups; 18-30 years of age and 31-60 years of age. Participant stature, body mass, BMI and lower leg length was recorded to determine the effect these factors had on sitting comfort when the participants were seated in different seating conditions. From the results obtained, it was found that, by altering seat height, seat pan angle, and backrest angle, passenger comfort can be optimised. Furthermore, it was found that certain combinations of seat height, seat pan angle and backrest angle are more beneficial with regards to saving aircraft cabin space. However, this means that a compromise needs to be found for SARA as passenger comfort needs to be optimised, whilst decreasing the use of cabin space to reduce costs.
Keywords: Uncatalogued